Peran Kepala KUA dalam Menentukan Hak Perwalian atas Anak Perempuan yang Lahir Akibat Hamil di Luar Pernikahan - Iskandar, Muhammad (Lembaga Intelektual Muda Maluku, 2024)
The focus of this research is to find out the role of the head in determining the guardianship rights of girls born due to pregnancy outside of marriage. Data collection was carried out through observation, interviews, and literature studies. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the study show that the role of the head in determining guardianship rights for girls born due to pregnancy out of wedlock: first as a deepening of the problem and the determination of the law. The Head of KUA Kotabumi Selatan studies the problem and determines the validity of the child, both outside and inside the legal marriage, then will determine his guardianship rights. Second, as a mediator and explanation of the problem, the Head of KUA Kotabumi Selatan will provide counseling to families as an effort to convey goals and provide proper understanding. As a solution provider, the Head of KUA Kotabumi Selatan will develop the best solution for the family in order to maintain a sense of honor by holding a wedding in two stages, namely the first stage at KUA and the second stage at the bride's house